Prognostic Value of Elevated Levels of Intestinal Microbe-Generated Metabolite Trimethylamine-N-Oxide in Patients With Heart Failure: Refining the Gut Hypothesis - TANG, W. H. Wilson; ZENENG WANG; YIYING FAN; LEVISON, Bruce; HAZEN, Jennie E; DONAHUE, Lillian M; YUPING WU; HAZEN, Stanley L (Journal of the American College of Cardiology, 2014)
Altered intestinal function is prevalent in patients with heart failure (HF), but its role in adverse outcomes is unclear. This study investigated the potential pathophysiological contributions of intestinal microbiota in HF. We examined the relationship between fasting plasma trimethylamine-N-oxide (TMAO) and all-cause mortality over a 5-year follow-up in 720 patients with stable HF. The median TMAO level was 5.0 μM, which was higher than in subjects without HF (3.5 μM; p < 0.001). There was modest but significant correlation between TMAO concentrations and B-type natriuretic peptide (BNP) levels (r = 0.23; p < 0.001). Higher plasma TMAO levels were associated with a 3.4-fold increased mortality risk. Following adjustments for traditional risk factors and BNP levels, elevated TMAO levels remained predictive of 5-year mortality risk (hazard ratio [HR]: 2.2; 95% CI: 1.42 to 3.43; p < 0.001), as well as following the addition of estimated glomerular filtration rate to the model (HR: 1.75; 95% CI: 1.07 to 2.86; p < 0.001). High TMAO levels were observed in patients with HF, and elevated TMAO levels portended higher long-term mortality risk independent of traditional risk factors and cardiorenal indexes.